The Daughter Industry - (:unkn) unknown (My University, 2018)
THE DAUGHTER INDUSTRY is a long creative work about reproduction. It works to demystify, narrate, and paradoxically to mythologize son-preference as it leads to the practice of sex-selection. The creative project examines transnational values and texts informing the practice and documents some consequences of the practice. This dissertation lifts language and images from medical textbooks, web pages, and various other sources. It also attempts to translate, rewrite, and treat found text. The poetics of THE DAUGHTER INDUSTRY manifests in a prismatic approach to its topic. It mixes engagements with collage, documentation, performance, (his)storytelling, prose, poem, prose poem, lyric, lyric address, and the lyric essay.